2016
DOI: 10.7883/yoken.jjid.2014.236
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir and Abacavir/Lamivudine in Japanese Treatment-Naïve and Treatment-Experienced Patients with HIV Infection: a 48-Week Retrospective Pilot Analysis

Abstract: SUMMARY: Abacavir/lamivudine (ABC/3TC) is a nucleoside reverse transcriptase inhibitor used for treating human immunodeficiency viral (HIV) infections. Hypersensitivity reactions such as skin eruptions caused by ABC are well-known, but rarely occur in Asians. Raltegravir (RAL) is an integrase strand transfer inhibitor, that is now increasingly, used for treating HIV infections because it has few adverse effects. This retrospective analysis assessed the efficacy and safety of combined ABC/3TC and RAL in both tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Abundant data from clinical trials and some real-life cohort studies in naïve patients indicate that the combination of RAL with FTC/TDF, and to a lesser extent with ABC/3TC, is highly efficacious and safe [ 12 14 ]. As a switching option, RAL has been studied mostly in combination with FTC/TDF [ 15 , 16 ], and available data associated with ABC/3TC are scarce [ 17 , 18 ], even though this regimen has been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Abundant data from clinical trials and some real-life cohort studies in naïve patients indicate that the combination of RAL with FTC/TDF, and to a lesser extent with ABC/3TC, is highly efficacious and safe [ 12 14 ]. As a switching option, RAL has been studied mostly in combination with FTC/TDF [ 15 , 16 ], and available data associated with ABC/3TC are scarce [ 17 , 18 ], even though this regimen has been widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, Suzuki et al and Kang et al, already mentioned with regard to treatment-experienced subjects, showed in their abovementioned studies optimal therapeutic effect of ABC/3TC plus RAL also in treatment-naı¨ve patients, even with pre-treatment viral loads >100,000 copies/mL. 6,7 As regards the safety of ABC/3TC þ RAL in treatment-naı¨ve patients, we did not observe any significant alteration in lipid profile, liver and renal function, in accordance with Suzuki et al 6…”
Section: Discussionmentioning
confidence: 82%
“…Similarly to our study, in other studies the switch to ABC/3TC plus RAL led to an improvement in lipid levels and liver function, particularly if the previous regimen contained a PI. 6,7,10,11 In the treatment-naı¨ve group, all five patients achieved viral suppression at the latest measurement, suggesting the efficacy of ABC/3TC plus RAL among treatment-naı¨ve patients. Three patients had pretreatment viral loads > 100,000 copies/mL, and all of them achieved viral suppression.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations